REST in practice - Webber, Jim (O'Reilly Media, 2010)
REST continues to gain momentum as the best method for building web services, leaving many web architects to consider whether and how to include this approach in their SOA and SOAP-dominated world. This book offers a down-to-earth explanation of REST, with techniques and examples that show you how to design and implement integration solutions using the REST architectural style. Explore several web communications approaches, and discover what makes REST different Walk through the pros and cons of the RESTful approach Learn how the underlying architecture of the Web can drastically simplify programming built on top of it View REST in the context of cloud computing and the Semantic Web Understand how hypermedia serves as a model for computers to process data.